2012
DOI: 10.1111/j.1365-2265.2012.04396.x
|View full text |Cite
|
Sign up to set email alerts
|

Time trend in tumour size and characteristics of anaplastic thyroid carcinoma

Abstract: The tumour size of ATC decreased, and cases with coexistent DTC increased over the last two decades. We found that patients with ATC showing long-term survival are those who had atypical presentations such as anaplastic transformation in early stage of DTC or small size of tumours without coexistent DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
3
23
2
Order By: Relevance
“…Anaplastic TC is a highly aggressive malignancy [28], whereas K1 papillary TC is well differentiated and has a good prognosis [29]. Squamous TC is an aggressive neoplasm which has a bad prognosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastic TC is a highly aggressive malignancy [28], whereas K1 papillary TC is well differentiated and has a good prognosis [29]. Squamous TC is an aggressive neoplasm which has a bad prognosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies have demonstrated longer survival rates compared to the past [4,24] and additionally evidence exists, obtained by in vitro experiments, of the effectiveness of certain drugs which exert on the one hand a cytoreductive effect on anaplastic clones, and on the other hand which favors redifferentiation, inducing the reacquisition of the ability to uptake 131 I [30e34]: this may render the clones susceptible to radiometabolic therapy with 131 I. In addition, the loss of anaplasia, may also render them less resistant to external radiotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…Anaplastic carcinomas and those which are poorly differentiated are neoplasms strictly found in advanced age, and are very rare in patients under 60 years of age [1e3]. They are very aggressive cancers with a high mortality rate [4].Well-differentiated carcinomas, on the other hand, are much more frequent compared to undifferentiated forms and have a good prognosis with low mortality rates and a survival rate which varies between 80% and 95% [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the wide use of high resolution US has provided early detection of thyroid malignancy, and this might contribute to an earlier detection of ATC. Han, et al38 reported time trends of tumor size and characteristics of ATC. They reported that the mean tumor size of ATC decreased significantly and the frequencies of coexistent differentiated thyroid cancer (DTC) increased over time.…”
Section: Discussionmentioning
confidence: 99%